2003
DOI: 10.3354/meps248055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the toxic dinoflagellate Alexandrium fundyense on the copepod Acartia hudsonica: a test of the mechanisms that reduce ingestion rates

Abstract: Reduced grazing on harmful algal bloom species has been attributed to both the feeding deterrence and toxicity of the algae. Both toxic and deterrent effects of dinoflagellates of the genus Alexandrium, which contain toxins that cause paralytic shellfish poisoning, have been reported on different copepod species. We examined how toxin-containing Alexandrium fundyense affected ingestion rates of 2 geographically distinct Acartia hudsonica (Copepoda: Calanoida) populations over short timescales. The copepod popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 44 publications
5
63
2
Order By: Relevance
“…tonsa was shown to be able to discriminate between different species of Alexandrium with different toxin content, with a significant preference for the least toxic species (Teegarden 1999; but see also Colin & Dam 2003). As far as we know, the present study is the first investigation using a single phytoplankton clone with variable PST content in order to investigate the feeding preference of grazing copepods.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…tonsa was shown to be able to discriminate between different species of Alexandrium with different toxin content, with a significant preference for the least toxic species (Teegarden 1999; but see also Colin & Dam 2003). As far as we know, the present study is the first investigation using a single phytoplankton clone with variable PST content in order to investigate the feeding preference of grazing copepods.…”
Section: Discussionmentioning
confidence: 97%
“…for 3 days to cover both fast (e.g. behavioural rejection and physical incapacitation ;Colin & Dam 2003) and slow (e.g. associative learning) mechanisms that may result in discriminate feeding of the copepods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Values below reference line indicate that A. anophagefferens is toxic and/or elicits avoidance rather than being of poor nutritional value relative to the control diet, based on the scheme proposed by Jónasdóttir et al (1998) to discriminate between toxicity and nutritional inadequacy 1987) or behavioral avoidance/deterrence from cues detected prior to ingestion. Colin & Dam (2003) have associated only the former mechanism to toxicity, in the context of algal species that contain endogenous toxins, such as the PSP-producer Alexandrium fundyense. However, these mechanisms may not be mutually exclusive, as behavioral deterrence may be elicited by a detectable toxic compound on the algal cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Colin and Dam (2003) found that toxic A. fundyense physiologically incapacitated non-resistant adult Acartia hudsonica, reducing their ability to feed effectively: diets containing only 20% toxic A. fundyense (by carbon, $50 lg CL )1 ) reduced the total ingestion rate of NJ Acartia hudsonica to near zero within 12 h of exposure. In our experiment, the treatment diet consisted of 25% A. fundyense and was provided at a higher concentration.…”
Section: Effects On Life History Traitsmentioning
confidence: 99%